NUMERICAL LITERACY APPROACH IN MATHEMATICS EDUCATION IN JUNIOR HIGH SCHOOL - Dewi Fawziawati (Universitas Indraprasta PGRI, 2022)
Mathematics is a basic science, both its applied aspects and its reasoning aspects have an important role in the effort to master science and technology. Seeing the importance of the role of learning mathematics in all fields of science, it is not surprising that the government is very concerned with the development of mathematics at all levels of education in Indonesia. This research is a type of qualitative research, using descriptive method. While the notion of qualitative research can be understood as a research procedure that utilizes data and has the aim of describing and analyzing events, social dynamics, phenomena and attitudes of individual and group perceptions of something, the results of this study explain that, mathematics as one of the most important subjects that must taught to students at every school level, is a benchmark in creating competitive human resources. In learning mathematics itself, various basic abilities are needed, including partial ability, numerical ability, verbal ability, reasoning ability and so on. Numerical ability is one of the intelligence factors that play an important role in learning mathematics. These abilities are special that students have, and are very closely related to numbers and can be observed when students work on math problems such as multiplication, addition, subtraction, division and taking roots. Therefore, the numerical ability of students must be considered and trained continuously, especially when the teaching and learning process is being carried out in the classroom